2020
DOI: 10.1155/2020/7608964
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Management of Type 2 Diabetes Mellitus Bone Fragility

Abstract: Individuals with type 2 diabetes mellitus (T2DM) have an increased risk of bone fragility fractures compared to nondiabetic subjects. This increased fracture risk may occur despite normal or even increased values of bone mineral density (BMD), and poor bone quality is suggested to contribute to skeletal fragility in this population. These concepts explain why the only evaluation of BMD could not be considered an adequate tool for evaluating the risk of fracture in the individual T2DM patient. Unfortunately, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 164 publications
(219 reference statements)
3
74
0
18
Order By: Relevance
“…Second, there might also be a lack of statistical power due to the small sample size, with 6 studies having less than 50 participants ( 12 , 14 , 15 , 19 , 20 , 22 ). Third, type 2 diabetes is, despite having an increased risk of fragility fractures, associated with a higher BMD and lower bone turnover markers ( 36 , 37 ). Improved glycemic control postsurgery in our study population of patients solely with type 2 diabetes could therefore explain greater changes in aBMD and bone turnover markers than in some of the studies including few or no patients with diabetes ( 12 , 13 , 15–19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there might also be a lack of statistical power due to the small sample size, with 6 studies having less than 50 participants ( 12 , 14 , 15 , 19 , 20 , 22 ). Third, type 2 diabetes is, despite having an increased risk of fragility fractures, associated with a higher BMD and lower bone turnover markers ( 36 , 37 ). Improved glycemic control postsurgery in our study population of patients solely with type 2 diabetes could therefore explain greater changes in aBMD and bone turnover markers than in some of the studies including few or no patients with diabetes ( 12 , 13 , 15–19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the prolonged use of thiazolidinediones (TZDs), such as pioglitazone and rosiglitazone, which activate peroxisome proliferator-activated receptor gamma (PPARγ), has been associated with negative effects on bone metabolism, despite a beneficial effect on glycemic control (reduced insulin resistance and improved insulin sensitivity). Specifically, by activating PPARγ, the use of TZDs leads to increased adipogenesis, decreased osteoblastogenesis while at the same time increasing osteoclastogenesis, and promotes osteocyte apoptosis, therefore resulting in decline in bone formation with enhancement of bone resorption ( 23 , 104 , 109 112 ), consequently poor bone biomechanical properties.…”
Section: Type 2 Diabetes Mellitus and Bonementioning
confidence: 99%
“…It has been observed that vitamin D supplementation in PCOS women may improve the steroidogenesis and enzymatic antioxidant activity in the human GC [ 94 ] and it may attenuate the actions of AGEs [ 95 , 96 ]. AGEs play a role in age-related bone loss [ 97 , 98 ]. AGEs provoke bone cell impairment and alter bone biomechanical properties.…”
Section: Vitamin D and Pcosmentioning
confidence: 99%
“…AGEs provoke bone cell impairment and alter bone biomechanical properties. Pentosidine (PENT), a well-characterized AGE, is even considered a predictor of bone fracture [ 97 ]. It has been reported AGEs interfere with osteoblast maturation, leading to morphological cell modifications, function failure, and inhibition of the calcification process.…”
Section: Vitamin D and Pcosmentioning
confidence: 99%